Evaluation of dieless hydroforming process for manufacturing of variable cross section tubular structures. (October 2022) - E, Chandrasekar; Mukherjee, Manidipto; Singh, Dilpreet; Subramanian, Chidambaram
The dieless hydroforming is a type of manufacturing method that forms materials using pressurised hydraulic fluid rather than dies and presses as in traditional hydroforming, resulting in significant cost savings. The dieless hydroforming of tubular structures with variable cross section has received little attention, indicating that more research is needed in this area. Therefore, this article investigated dieless hydroforming of low carbon steel material with fluid pressures ranging from 10 to 50 bar and sheet thicknesses ranging from 1 to 2.5 mm to produce tubular structures with variable cross section. The main goal is to comprehend the deformation characteristics in relation to the parameters, as well as the impact of deformation on the microstructural and mechanical behaviour. The inflation and contraction patterns of hydroformed structures are numerically determined using the finite element method at various parameters and then compared to experimental results which show a good correlation. Plastic deformation induced grain refinement in all deformed samples, as compared to as-received material. The sample hydroformed at 30 bar and with a thickness of 2.5 mm showed higher yield strength (291 MPa), tensile strength (404 MPa) and elongation (48%) than the other samples. Hydroformed tubular structures with variable cross section are created and used in electric poles to hold solar panels after the process repeatability is tested and found to be highly repeatable with greater than 97% accuracy.